Patience and time consistency in collective decisions - Denant-Boemont, Laurent; Diecidue, Enrico; l’Haridon, Olivier (Experimental economics : a journal of the Economic Science Association, 2017)
We present experimental evidence regarding individual and group decisions over time. Static and longitudinal methods are combined to test four conditions on time preferences: impatience, stationarity, age independence, and dynamic consistency. Decision making in groups should favor coordination via communication about voting intentions. We find that individuals are neither patient nor consistent, that groups are both patient and highly consistent, and that information exchange between participants helps groups converge to stable decisions. Finally we provide additional evidence showing that our results are driven by the specific role of groups and not by either repeated choices or individual preferences when choosing for other subjects.